THE EMERGENCE OF LA DECROISSANCE - Anca Elena Gheorghica (CES Working Papers, 2012)
The paper aims to provide an overview of the emergence of degrowth – the notion designates a grass root, political and academic movement which is progressively spreading since the previous decade across Europe as a reaction to the drawbacks associated with the imperatives of economic growth. The intellectual founder of the new paradigm of degrowth is the Romanian born economist – Nicholas Georgescu-Roegen. The translation of his scientific works and the publication in French was to become the first milestone of degrowth discourse France becoming the cradle of the movement. While degrowth encompasses many dimensions such as equity, ecology, democracy or enjoyment of life, the overarching theme of the movement is the escaping of the economy as a central societal value. Degrowth gained an increasing audience in the beginning of the years 2000’, spreading progressively mostly in other Francophone, Francophile or Latin language speaking countries such as Italy and Spain, but in other European nations as well.